Options to reform the European Union legislation on GMOs - scope and definitions - Eriksson, Dennis; Custers, René; Edvardsson Björnberg, Karin; Hansson, Sven Ove; Purnhagen, Kai; Qaim, Matin; Romeis, Jörg; Schiemann, Joachim; Schleissing, Stephan; Tosun, Jale; Visser, Richard G. F. (Trends in biotechnology, 2020)
We discuss options to reform the EU genetically modified organisms (GMO) regulatory framework, make risk assessment and decision-making more consistent with scientific principles, and lay the groundwork for international coherence. The first in a three-part series, this article focuses on reform options related to the scope of the legislation and the GMO definition.